Feasibility of Rapidly Developing and Widely Disseminating Patient Decision Aids to Respond to Urgent Decisional Needs due to the COVID-19 Pandemic. (February 2021) - Stacey, Dawn; Ludwig, Claire; Archambault, Patrick; Babulic, Kevin; Edwards, Nancy; Lavoie, Josée; Sinha, Samir; O'Connor, Annette M.
To meet urgent decisional needs of retirement/nursing home residents and their families, our interdisciplinary stakeholder team rapidly developed and disseminated patient decision aids (PtDAs) regarding leaving one's residence during the COVID-19 pandemic. The development steps were as follows: identify urgent decisional needs, develop PtDAs using the Ottawa Decision Support Framework template and minimal International PtDA Standards, obtain stakeholder feedback, broadly disseminate, and incorporate user feedback. Within 2 wk, we developed 2 PtDAs for retirement and nursing home living environments that were informed by decisional needs (identified from public responses to related media reports), current pandemic regulations/guidance, and recent systematic reviews. Within 3 wk of their dissemination (websites, international PtDA inventory, Twitter, Facebook, media interviews), the PtDAs were downloaded 10, 000 times, and user feedback was positive. Our expert team showed feasible rapid development and wide dissemination of PtDAs to respond to urgent decisional needs. Development efficiencies included access to a well-tested theory-based PtDA template, recent evidence syntheses, and values-based public responses to media reports. Future research includes methods for rapidly collecting user feedback, facilitating implementation, and measuring use and outcomes.